Strategy and Coherence of a Program of Regional Development: A Methodology for synergy evaluation - Tomas Mancha; Ruben Garrido; Juan R. Cuadrado-Roura (European Regional Science Association (ERSA), 1998)
The main purpose of this paper is to present a methodological proposal to value the synergy in programmes of regional development, regarding either their objectives or their performances. First, the main aspects of the methodology used to evaluate individually the synergy of the objectives (performances) are set out by using a Delphi technique. This technique allows to build a matrix of weights, according to the degree of synergy for every objective (performance). Then, hierarchical clusters are applied in the data processing. This technique leads to a ranking of objectives which shows the strategic value of the programme subject to evaluation. The methodological analysis shows also an application of the Community Support Framework ( 1994-1999) for the Spanish Objective 1 regions.
Keywords: 330